2018
DOI: 10.4132/jptm.2017.10.17
|View full text |Cite
|
Sign up to set email alerts
|

The Significance of TROP2 Expression in Predicting <i>BRAF</i> Mutations in Papillary Thyroid Carcinoma

Abstract: Pancreatic cancer is one of the most devastating human malignancies. Despite considerable research efforts, it remains resistant to almost all available treatment regimens. The human trophoblast cell-surface antigen, TROP2, was found to be strongly expressed in a variety of human epithelial cancers, correlating with aggressiveness and poor prognosis. TROP2 antigen expression was investigated retrospectively by immunohistochemistry in paraffin-embedded primary tumour tissue samples from a series (n ¼ 197) of co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 22 publications
1
10
0
Order By: Relevance
“…Previous studies have linked TROP2 to increased tumor growth and demonstrated TROP2 to be a candidate tumor prognostic marker in various tumors. TROP2 is found to be overexpressed in the majority of human epithelial cancers, including pancreatic cancer, gastric cancer, lung cancer, ovarian cancer, and colorectal cancers (10,14,32). Chen et al (33) investigated the expression of TROP2 and epithelial-mesenchymal transition (EMT) indicator proteins in 93 patients with gallbladder cancer (GBC) and demonstrated that increased expression of TROP2 in GBC is associated significantly with aggressive progression and poor prognosis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies have linked TROP2 to increased tumor growth and demonstrated TROP2 to be a candidate tumor prognostic marker in various tumors. TROP2 is found to be overexpressed in the majority of human epithelial cancers, including pancreatic cancer, gastric cancer, lung cancer, ovarian cancer, and colorectal cancers (10,14,32). Chen et al (33) investigated the expression of TROP2 and epithelial-mesenchymal transition (EMT) indicator proteins in 93 patients with gallbladder cancer (GBC) and demonstrated that increased expression of TROP2 in GBC is associated significantly with aggressive progression and poor prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…Human trophoblast cell surface antigen 2 (TROP2) is a 36-kDa single-pass transmembrane protein encoded by the tumor-associated calcium signal transducer 2 (Tacstd2) gene, with low to no expression in normal tissues (10)(11)(12)(13). Accumulating studies have demonstrated TROP2 to be a candidate tumor prognostic marker, which was highly expressed by various tumors, such as pancreatic cancer (14,15), gastric cancer (11,16), lung cancer (17,18), ovarian cancer (19), and colorectal cancers (20).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Its overexpression is seen in the majority of human carcinomas, including colorectal, gastric, and pancreatic adenocarcinoma, squamous cell carcinoma of the oral cavity, non-small cell carcinoma of the lung, and endometrial and ovarian cancers, and rarely in normal tissue. TROP-2 overexpression in carcinoma is related to poor prognosis and aggressive behavior [6, 8, 11], but no single marker is sensitive nor specific for differentiation between benign and malignant thyroid neoplasm. Therefore, in this study, we evaluated the diagnostic utility of a panel consisting of HBME-1 and TROP-2 for differentiation between benign and malignant thyroid lesions.…”
Section: Introductionmentioning
confidence: 99%
“…HBME-1 is a membrane antigen found in the mesothelial cells and in lung, breast, and pancreas adenocarcinomas. TROP-2, also known as tumor-associated calcium signal transducer 2 (TAC-STD2) [6, 8, 11], is a 35-kDa, 323 amino acid, type 1 transmembranous glycoprotein. It is identified in choriocarcinoma and trophoblastic cells.…”
Section: Introductionmentioning
confidence: 99%